The experiences of patients with schizophrenia on smoking and cessation: a qualitative study - Seki Öz, Hilal; Taktak, Şafak (Journal of Dependence, 2024)
Objective: Compared to the general population, patients with schizophrenia have high smoking rates and low smoking cessation rates. The aim of this study was to explore the experiences of patients with schizophrenia regarding smoking and quitting. Method: The study was carried out based on the phenomenological design, one of the qualitative research methods. Purposeful sampling method was used in the research, and in-depth interviews were conducted with 15 smokers using a semi-structured interview form. Results: In the thematic analysis, 4 themes, "Effects of schizophrenia", "Coping with smoking", "Factors affecting smoking", "Barriers to quitting smoking" and 13 sub-themes were determined. With the research, it has been seen that those with schizophrenia tend to smoke to cope with the problems caused by the disease, drug treatments, boredom, loneliness and emotional intensity. Some patients are reluctant for smoking cessation, some do not have sufficient motivation and medical support. Conclusion: In order to prevent the multidimensional problems caused by smoking, it is recommended to conduct intervention studies that enable to manage the factors that increase smoking, strengthen the factors that reduce smoking and encourage smoking cessation.